PENGABDIAN MASYARAKAT : JENIS TANAMAN OBAT, DESAIN PERANCANGAN DAN PELAKSANAAN TAMAN TOGA - Choirul Amin; Rizka Tri Arinta (LPPM Universitas 17 Agustus 1945 Semarang, 2022)
Traditional family medicinal plants or herbs or often abbreviated as Toga, are very beneficial for health and when planted around the house create a beautiful environment. Currently, people prefer to use chemical-based medicines for several reasons, including: the first is the lack of knowledge about medicinal plants, the second is the limited land for growing family medicinal plants, third, the lack of information dissemination about family medicinal plants on easily accessible media. or informative to citizens.From some of the problems above, we can draw the main points of the problems that are discussed and this writing tries to find ways to provide education to the community in terms of the types of family medicinal plants, as well as the design and implementation of the construction of the toga garden.The scope of this paper is related to the author's discipline, namely in the architectural realm and takes a case study on an empty land next to a security post located in RT 08, RW V, Sumurboto Village, Banyumanik District, Semarang.The purpose of writing related to knowledge of the types of family medicinal plants, toga garden designs and their implementation are: first so that people know about the types and benefits of family medicinal plants, second so that people understand the importance of family medicinal plants for health, third so that people maximize and utilize the land. that exist in their respective environments.